The Expected Impact of joining Regional Seed Cooperation for Vietnam and the Philippines - International Potato Center (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Seeds are the foundation for agriculture. Access to good-quality seeds of crop varieties that are adapted to the needs and production systems of farmers is an essential feature of sustainable crop production. A sustainable seed system ensures that farmers have timely access to affordable good-quality seeds and planting materials of the most suitable crop varieties. Farmers, especially small-scale farmers in developing countries, often lack or have limited access to affordable, good-quality seeds and planting materials of crop varieties that are adapted to their production systems and growing conditions. This is because of a lack of supply and inefficient distribution, inadequate quality assurance systems, and bottlenecks caused by a lack of enabling seed policies. Moreover, if seeds are of poor quality, there could be poor crop establishment, higher incidence of pests and diseases, and, ultimately, low yield. Given the uncertainties of climate change, sustainable seed systems must ensure that farmers’ changing needs form the breeding objectives of research institutions to develop the most suitable and best adapted varieties. Through efficient seed production and distribution systems, farmers can take advantage of the benefits of these elite varieties. Countries need responsive mechanisms (including different forms and scales of seed enterprises and community-based production and distribution systems) for ensuring that farmers have access to good-quality seeds and planting materials of crop varieties that are adapted to their needs. The effects of climate change are highly visible around the world, Vietnam and the Philippines are no exception. Land productivity is on the decline due to processes of accelerated erosion and poor governance, while the incidence of pests and diseases is markedly increasing. To make things worse, farmers often do not have timely access to appropriate planting materials, and they move to urban areas to pursue other non-agricultural livelihoods. In the era of globalization, it is important to contextualize the constraints faced in the Philippines and Vietnam having potential influences on other regions, and vice versa. We must refrain from thinking of any country as an isolated region and draw parallels from the experiences of farmers in one country with those in other regions where climate change continues to threaten people’s food security and agro-climatic conditions are comparable.